Atributos químicos do solos em áreas cultivadas com urucum, guaraná, cupuaçu e floresta no assentamento São Francisco em Canutama-AM - Rodrigues, Ludmilla Colares (2021)
In the Amazon region, the predominant soils are characterized by its high degree of weathering with strong nutritional limitations. 30% to 50% of natural vegetation occurs on infertile soils, so when there is change from natural vegetation to agricultural exploitation system, the new agricultural areas are already starting in infertile soil, causing impacts negative or positive in the environment depending on the management adopted and the selected crops. A key tool to ascertain the impact of forest/agriculture conversion is the multivariate analysis, which describes the behavior of simultaneous multivariate data. So, the objective is in this work to evaluate the chemical attributes of the soil in areas cultivated with annatto, guaraná, cupuaçu and forest in Red-Yellow Argisol in the settlement San Francisco in Canutama, AM. The study will be developed in São Francisco settlement located in the city of Canutama-AM, in four areas, three of which are currently cultivated with Urucum, Cupuaçu, and Guarana and a forest area. For each area a mesh will be established. 90 m x 70 m with regular spacing of 10 m between sampling points. The soils will be sampled at the crossing points of the meshes, under the 0.00-0.05 layers; 0.05-0.10; and 0.10-0.20 m, totaling 240 samples per area. Chemical analyzes of: pH (in water and KCl), acidity will be performed potential, exchangeable aluminum, calcium, magnesium, phosphorus, potassium and sodium. To assess the joint action of chemical attributes on discrimination of the environments studied, descriptive statistics and analysis will be applied. multivariate statistics.